Common Factors in Equity Option Returns - Horenstein, Alex; Vasquez, Aurelio; Xiao, Xiao (Review of Financial Studies, 2026)
We explore the factor structure in delta-hedged equity option returns. A sparse latent factor model generates a correlation of 0.90 or higher between average and predicted option returns. A comparable performance is achieved with a characteristic-based model containing four factors: the equally weighted option portfolio, a factor based on the difference between historical and implied volatilities, a factor based on the ratio of corporate cash holdings to the total value of the firm’s assets, and a factor based on volatility of volatility. Traditional stock return factors cannot explain these option factors.